Analyzing operational risks of a recyclable waste-based payment public transit system in Surabaya, Indonesia - Anityasari, Maria; Wessiani, Naning Aranti; Pratiwi, Atikah Aghdhi; Putri, Fathaliati Zikri Musev; Rinardi, Hilmi Cahya; Prakoso, Matheus Bimo Aryo; Ghaisani, Nofinda (Universitas Serang Raya, 2025)
Suroboyo Bus, a municipal public transportation initiative managed by the Surabaya Department of Transportation (SubDOT) in Indonesia, was launched to promote the use of public transit by accepting recyclable plastic waste as transit fare payments. However, this transportation system presented challenges, as prior to 2019, Suroboyo Bus performed its operational activities without adequately incorporating operational risk, specifically considering Health, Safety, and Environment (HSE) factors. The analysis of risk profiles and a mitigation plan concerning the well-being of both their staff and passengers was uncomprehensive. To address these issues, this paper evaluates the operational risk based on ISO 31000:2018, the Failure Mode and Effect Analysis (FMEA), and the Benefit Cost-Analysis (BCA). The analysis identified 114 risks and 189 combinations of risks and impacts across 70 business processes associated with Suroboyo Bus operations, with varying degrees of risk severity. Risk prioritization analysis was performed using the Pareto 80:20 principle. Proposed risk response strategies include avoidance, mitigation, transfer, and tolerance. Evaluation of the feasibility of these strategies through benefits and cost analysis, supplemented by a sensitivity analysis, revealed Benefit-Cost Ratio (BCR) values ranging from 1.041 to 1.471, indicating that the proposed mitigation plan is feasible for all evaluated scenarios. These findings underscore the importance of implementing risk mitigation measures to improve the sustainability and effectiveness of the Suroboyo Bus service. Future research should explore the digital application developed for Suroboyo Bus passengers as part of the business process named “Golek Bis” (GOBIS) and other methods that can be used to enhance the quality and comprehensiveness of risk management.